Developing a new hybrid MCDM method for selection of the optimal alternative of mechanical longitudinal ventilation of tunnel pollutants during automobile accidents - Hashemkhani Zolfani, Sarfaraz; Esfahani, Mohammad H.; Bitarafan, Mahdi; Zavadskas, Edmundas K.; Arefi, Shahin L. (Transport, 2013)
Breathable air inside the tunnel is an undeniable necessity and beside natural ventilation, the tunnel should be reliably organized, to automatically provide healthy air under different conditions. Among methods of tunnel ventilation, longitudinal and transverse modes are the most common mechanical methods. This research is focused on selection of the optimal method for mechanical longitudinal ventilation of tunnel pollutants from four presented models. In terms of this research, the authors used SWARA (Step-wise Weight Assessment Ratio Analysis) as one of the most versatile MCDM (Multiple-Criteria Decision-Making) methods for managerial decision making in complex situations with multiple and varied measures. Fourteen experts of different fields were involved. The research model was established based on expert ideas and the following criteria: smoke control (C 1), safety level (C 2), design complexity (C 3), investment costs (C4), increasing concentration of pollutants until portal (C5), smoke laden section (C6) and simultaneous evacuation and fire fighting (C7). SWARA method was applied to evaluate criteria while VIKOR (VlseKriterijumska Optimizacija I Kompromisno Resenje) method was used to evaluate and rank four alternatives of this research, namely: 1) jet fans with spot extraction by axial fans (A1); 2) axial fans with Saccardo nozzle (A 2); 3) jet fans with shaft axial fans (A 3); 4) jet fans only (A 4). Final results illustrate that jet fans with spot extraction by axial fans is the best choice. Finally, the authors believe that this new hybrid model of MCDM methods can be useful as a new framework in different fields of research.First Published Online: 03 Apr 2013